Transgenic Expression of Synthetic Coat Protein and Synthetic Replication Associated Protein Produces Mild Symptoms and Reduce Begomovirus-Betasatellite Accumulation in Nicotiana benthamiana - Rasool, Ghulam; Yousaf, Sumaira; Ammara, Um e; Iqbal, Adnan; Saeed, Muhammad; Amin, Imran; Mansoor, Shahid (Frontiers in Agronomy, 2021)
Cotton (Gossypium hirsutum L.) is the most essential fiber crop and is widely cultivated within the tropical regions of the world. It has a major impact on socio-economical get-together in Pakistan. Unfortunately, it has been tormented by cotton leaf curl disease (CLCuD) that is produced by distinct species of begomoviruses (Family; Geminiviridae) like Cotton leaf curl Kokhran virus (CLCuKoV) associated with specific betasatellite—Cotton leaf curl Multan betasatellite (CLCuMuB). Host resistance against CLCuD has not achieved yet. The present study employed the use of synthetic genes considering the phenomenon of pathogen derived resistance (PDR). The coat protein (CP) and replication associated protein (Rep) genes sequence from Cotton leaf curl Kokhran virus-Burewala strain (CLCuKoV-Bu) was codon optimized, synthesized and used to control CLCuKoV-Bu and associated begomoviruses related to CLCuD. The Nicotiana benthamiana plants were Agrobacterium mediated transformed with synthetic CP (CPsyn) and synthetic Rep (Repsyn) under the control of Cauliflower mosaic virus 35S promoter. The transgenic plants harboring CPsyn, Repsyn genes were infiltrated with CLCuKoV alone and CLCuKoV- CLCuMuB inoculums showed relatively milder symptoms as compared with wild sorts and low virus concentration as checked by southern hybridization. The results confirmed that CPsyn, Repsyn genes may be utilized for the resistance of CLCuKoV and other begomoviruses related to CLCuD and PDR mechanism may also be developed for the control of CLCuD.